The Dialectic of Visual Arts Life in West Sumatra 1986-2003 - Nessya Fitryona (IJCAS (International Journal of Creative and Arts Studies), 2017)
West Sumatera is one of areas in the visual arts development in Indonesia. In 1980-1990s, there were found the presence data about installation of art and some alternative art works in art institutions and in public. The emergence that art works caused the struggle of the view of art practices in art society. That struggle seemed to thaw since emergence of Komunitas Seni Belanak (2003). This research explained the process of view of art practices that were occurred in West Sumatra which had changed from 1986 until 2003. This research used the concept of historical movement by Hegel dialectics theory and sociohistorical approach. The changing process of the art practices started from antithesis phase which was divided into two periods. The first antithesis period was the arrival of Agus Purwantoro (1986-1999). The second was the movement of IKIP Padang college students (1995-2003) and continued to the emergence of Komunitas Seni Belanak. The results of this study was the struggles in view of art practices in 1986 until 2003 was important as the transition period between the practices of modern art and the development of contemporary art in West Sumatra.